Microbial Metabolite Sodium Butyrate Attenuates Cartilage Degradation by Restoring Impaired Autophagy and Autophagic Flux in Osteoarthritis Development - Zhou, Haikang; Li, Guoqing; Wang, Yang; Jiang, Rendong; Li, Yicheng; Wang, Huhu; Wang, Fei; Ma, Hairong; Cao, Li (Frontiers in Pharmacology, 2021)
Osteoarthritis (OA) is a degenerative joint disease with multiple etiologies that affects individuals worldwide. No effective interventions are currently available to reverse the pathological process of OA. Sodium butyrate (NaB), a component of short-chain fatty acids (SCFAs), has multiple biological activities, including the attenuation of inflammation and anti-tumor activities in various diseases. However, whether the protective effects of NaB in OA are associated with the promotion of autophagy had not been investigated. Here, we explored the chondroprotective properties of NaB in an interleukin (IL)-1β-induced inflammatory chondrocyte model and an anterior cruciate ligament transection (ACLT) mouse mode. Hematoxylin and eosin (HE), Safranin O, and immunohistochemical staining were performed to evaluate the effects of NaB treatment on articular cartilage. An optimal NaB dose for chondrocyte treatment was determined via cell counting kit-8 assays. Immunofluorescence and transmission electron microscopy were used to detect autophagy in chondrocytes. Flow cytometry was utilized to detect reactive oxygen species (ROS), cell cycle activity, and apoptosis in chondrocytes. Western blot and immunostaining were performed to evaluate the protein expression levels of relevant indicators. We found that the administration of NaB by oral gavage could attenuate cartilage degradation. In parallel, NaB treatment could enhance the activation of autophagy, increase autophagic flux, decrease extracellular matrix degradation, and reduce apoptosis by restraining inflammation, ROS production, and cell cycle arrest in IL-1β-treated chondrocytes. The protective effects of NaB could be partially abolished by the autophagy inhibitor 3-methyladenine (3-MA), which indicated that the protective effects of NaB against OA were partially governed by the enhancement of autophagy to restrain the formation of inflammatory mediators and ROS and regulate cell cycle progression and apoptosis in chondrocytes. In conclusion, NaB could attenuate OA progression by restoring impaired autophagy and autophagic flux via the phosphoinositide 3-kinase (PI3K)/protein kinase B (Akt)/mammalian target of rapamycin (mTOR) pathway, both in vitro and in vivo, implying that NaB could represent a novel therapeutic approach for OA.